Regional Characteristics and Typical Circulation of Extreme Precipitation in the Warm Season over the Central and Eastern Qinghai-Xizang Plateau - Shuangxing LI; Hui WANG; Dongliang LI; Lian CHEN; Yuanchun JIANG (Gaoyuan qixiang)
Based on NCEP/NCAR reanalysis data and the daily precipitation data from 105 meteorological stations in the central and eastern Qinghai-Xizang Plateau from 1982 to 2020， we investigate the spatiotemporal anomalous characteristics and major falling areas of warm season extreme precipitation and typical circulation of large-scale extreme precipitation in the central and eastern Qinghai-Xizang Plateau.The results show that： （1） Total precipitation of central and eastern Tibetan Plateau in the warm season shows statistically significant increasing at the rate of 10.7 mm·（10a）-1 （P<0.05） during 1982 -2020， but there are obvious interdecadal trend shifts in the late 1990s and late 2000s.The increase in extreme precipitation of central and eastern Qinghai-Xizang Plateau is most prominent after 2009， and the climate tendency rate is of 4~5 times greater than that of during 1982 -2020.In terms of the distribution of spatial climate tendency rates， the trend of extreme precipitation in the southern Qinghai-Xizang Plateau is opposite to that in the central and northern Qinghai-Xizang Plateau in the three periods.The increase of extreme precipitation in the northern Qinghai-Xizang Plateau is the most prominent during 1998 -2009， and the extreme precipitation in the southern Qinghai-Xizang Plateau experiences the interdecadal trend shifts of significant increase， significant decrease and significant increase.（2） The small-scale extreme precipitation in central and eastern Qinghai-Xizang Plateau shows statistically significant decreasing trend （P<0.1）， while the large-scale extreme precipitation exhibits statistically significant increasing trend （P<0.05） during 1982 -2020.According to the locations of precipitation center， the level 4 large-scale extreme precipitation can be divided into three types， that is， northeast type （A type）， southern type （B type） and southeastern type （C type）.（3） The difference of location and intensity of the West Pacific Subtropical High is the main factor， which leads to the difference of water vapor sources and the locations of large-scale extreme precipitation falling areas.When the A-type large-scale extreme precipitation occurs， the West Pacific Subtropical High is anomaly weaker and eastward， which leads to the water vapor mainly transported from the Pacific Ocean and the westerlies.When the B-type occurs， the West Pacific Subtropical High is anomaly stronger and extending westward and southward， consequently， the water vapor mainly transported from the Indian Ocean and the Bay of Bengal.When the C-type occurs， the West Pacific Subtropical High is anomaly stronger， extending from the westward and northward， resulting in the water vapor mainly transported from the northwest Pacific Ocean， the South China Sea and the Bay of Bengal.